Tarekat dan Perubahan Sosial di Banten - Zaenal Muttaqin; Hamid Nasuki; Masri Mansoer (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2023)
This article aims to describe the involvement of Sufism orders (Tariqa) in the pace of social change in Banten. The main focus to be presented in this research article is how the Tariqa exists and develops in the life of Banten community and how the Tariqa plays a role in the social change. The method used in this study is a field research method with data collection techniques in the form of observation, interviews, and documentation analysis of literary sources. The article’s research recorded findings that various Sufism organizations or Tariqa had existed and became important actors of social change in Banten’s historical phases since the era of the Banten Sultanate, Western colonialism, until Banten became part of Indonesian territory in the contemporary era. Furthermore, the role of the Tariqa in social change is expressed in three transmissions of its influence in Banten, namely 1) the presence of Sufism teachings as a source of inspiration for the Sultan’s (ruler’s) policies, 2) the establishment of Sufi-sultan teacher connections (ruler/government), and 3) the existence of Sufi scholars and Tariqa organizations as the basis of social and moral movements.